"Behind every woman in prison is a man": Incarcerated Women's Perceptions of How We Can Better Help Them in the Context of Interpersonal Victimization. Issue 3 (2nd September 2018) - Kennedy, Stephanie C.; Mennicke, Annelise M.
ABSTRACT: Although women's rates of incarceration have increased dramatically, the criminal justice system does not meet women's unique needs. This article used qualitative methods to describe the responses of 113 incarcerated women to the following question: How can we better help women like you? Analyses focused on women's experiences of victimization and highlighted how to address trauma in prison reform and abolition efforts. Women suggested how victimization fueled their criminal offending behavior, detailed re-victimization in the prison milieu, and identified program gaps during custody and after release. Opportunities for immediate action include policy advocacy, mitigation, and shifting to a trauma-informed correctional approach.